ASYMMETRIC INDUCTION IN CATALYZED SYNTHESIS OF ORGANIC COMPOUNDS AS AN IMPORTANT STAGE IN THE EVOLUTION OF LIFE ON EARTH - Suslov E.V.; Khomenko T.M.; Il'ina I.V.; Korchagina D.V.; Komarova N.I.; Volcho K.P.; Salakhutdinov N.F. (My University, 2006)
It is shown that natural chiral catalysts, which could be formed e.g., from optically active amino acids on basic natural minerals, could lead, at early stages of evolution, to the formation of rather complex optically active products from starting achiral compounds. Using biomimetic combinations of vanadium ion complexes and chiral ligands synthesized from widely occurring natural compounds, we created novel catalytic systems, permitting the transfer of optical activity in the course of catalytic chemical transformations of achiral compounds. We found that in the presence of natural clay, optically active terpenoids from the pinane series undergo multistage transformations, forming unexpected new products with preservation of optical purity. © Pleiades Publishing, Inc. 2006.